Pelaksanaan Layanan Pendidikan Bagi Anak Berkebutuhan Khusus Di Slb Rela Bhakti 1 Gamping Sleman - Nailatun Nisa; Siti Uswatun Khasanah; An-Nisa Apriani; Zahri Hidayat A Berna (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
He provision of educational services for children with special needs requires adaptive approaches that accommodate students’ characteristics and learning needs. Special schools play an essential role in delivering educational services that support the academic, social, and emotional development of students with special needs. This study aims to describe the implementation of educational services for children with special needs at SLB Rela Bhakti 1 Gamping Sleman, particularly at the SDLB level. This research employed a descriptive qualitative approach involving the principal, classroom teachers, and students with mild and moderate intellectual disabilities as research subjects. Data were collected through observation, semi-structured interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that educational services at SLB Rela Bhakti 1 Gamping Sleman are implemented adaptively through limiting the number of students in each class, developing an independent curriculum based on a deep learning approach, and applying concrete and contextual learning methods and media. The main challenges in the learning process are related to students’ emotional conditions and social dynamics among peers. Efforts to address these challenges include flexible learning strategies, support from the school principal, and collaboration with parents. These findings suggest that adaptive, flexible, and collaborative educational services play an important role in supporting the development of children with special needs.